Expansion of invasive seed beetle Megabruchidius dorsalis Fahreus, 1839 (Coleoptera, Chrysomelidae, Bruchinae) in the Turkestan Region (South Kazakhstan) - I.I. Temreshev; A.M. Makezhanov (Acta Biologica Sibirica, 2019)
An invasive seed beetle species Megabruchidius dorsalis Fahreus, 1839 has been known since 2016 in southeastern Kazakhstan (Almaty city and surrounding area) and now it could be registered everywhere where it host plants grow. In Turkestan oblast, we previously found it only in Shymkent city, and we assumed that it could be further settled in suburbs and in Turkestan oblast (Temreshev, 2017b). In Turkestan region (southern Kazakhstan) we found this species in the city of Kentau and its surroundings. The individuals we found were of different sexes. The Gleditsia triacanthos seeds we collected were damaged by 10% only. This allows us to conclude that the species has already been introduced in the Kentau urban agglomeration, but has not yet reached its maximum abundance and continues to gradually settle within it. This indicates an expansion of the pest range within the south of the country. The invasion of the species came from the city of Shymkent (southern Kazakhstan), where the species in turn came from Almaty (southeast Kazakhstan), from where it has been known since 2016.